PENGARUH STRES KERJA DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN DI PT. SENTRA ADI PURNA BENGKULU - Hermawati Hermawati; Syofian Syofian (Creative Research Management Journal, 2021)
his research is included in associative/relationship research, which is a study that aims to determine the relationship between the effect of work stress and workload on employee performance at PT. Adi after Bengkulu center. This study tries to determine the factors that affect employee performance in the construction service business of PT. Adi Purna Center. The population in this study were all permanent employees working at PT. Adi Purna Center as many as 30 people and the sample amounted to 30 people. The sampling technique is saturated, all the population becomes the research sample with a questionnaireinstrument. The purpose of this study was to analyze the effect of each variable, work stress (X1), and workload (X2), on employee performance (Y). From the calculation results obtained a linear regression equation, which is where from the equation it canbe interpreted that there is an influence between the two variables. The value of the correlation coefficient (r) and the coefficient of determination (r2) shows the effect of workload on employee performance is very strong. Constant (a) employee performance has decreased . Regression coefficient (b) each employee's performance has decreased as well as degrees of freedom, meaning the hypothesis which states that work stress and workload have a positive effect on employee performance at PT. Adi Purna CenterBengkulu.